Pengaruh Motivasi Intrinsik dan Ekstrinsik terhadap Loyalitas Karyawan melalui Work Engagement sebagai Variabel Intervening (Studi Kasus Wisata Lawang Sewu di Kota Semarang) - Aditya, Mohamad Rifki Deska; Irawan, Bahrain Pasha (ARZUSIN, 2026)
This study was motivated by the declining number of tourists at the Lawang Sewu tourist attraction in Semarang, which has affected operational efficiency and workforce reductions, thereby potentially decreasing employee loyalty. This study aimed to analyze the effect of intrinsic motivation and extrinsic motivation on employee loyalty through work engagement as an intervening variable. This study used a quantitative approach with an explanatory research type. The research sample consisted of 100 employees of the Lawang Sewu tourist attraction in Semarang selected using purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) through SmartPLS version 4. The results showed that intrinsic motivation and extrinsic motivation had a positive and significant effect on employee loyalty. Both forms of motivation were also proven to have a positive and significant effect on work engagement. In addition, work engagement had a positive and significant effect on employee loyalty and was able to mediate the effect of intrinsic motivation and extrinsic motivation on employee loyalty positively and significantly. Thus, this study affirms that improving employee loyalty can be achieved through the continuous strengthening of intrinsic motivation, extrinsic motivation, and work engagement. The practical implications of this study indicate the importance of human resource management strategies that can maintain employee work engagement amid the dynamics of declining tourist visits and operational efficiency.